An Analysis of the Factors Contributing to Slum Development from the Perspective of Sustainable Settlements in Ngrampal Subdistrict, Sragen Regency - Samudra, Rafif Aswidar; Suminar, Lintang; Rahayu, Murtanti Jani (Journal of Geosciences and Environmental Studies, 2025)
Sragen Regency is one of the regencies experiencing regional development by facing challenges in infrastructure distribution. One of the manifestations of these challenges is the presence of slum areas, namely the Ngrampal slum. This study aims to determine the existing conditions and factors that influence the existence of Ngrampal slums in the perspective of sustainable settlements, using quantitative methods through a deductive approach. This research uses quantitative methods, with data collection techniques through observation, questionnaires, and institutional surveys. The data analysis technique used was Exploratory Factor Analysis (EFA). This research has resulted in new factor groups regarding the factors that influence the existence of slums in Ngrampal slums: 1) infrastructure factors and cultural preservation efforts and 2) spatial factors and environmental-social conditions of the community. With these results, attention to the maintenance, availability, and affordability of basic settlement infrastructure is one of the important steps to improve community welfare. In addition, development is also important to improve the environmental and social quality of the community.